Exploring The Effect of Testosterone Hormonal Therapy on Sexual Problems in Postmenopausal Women: A Comprehensive Systematic Review on Clinical Trials - Amri, Zidan Dzulyadain; Putri, Annisa Reanimasi Asmoro; Amanda, Nasyabila Anryandi; Torrences, Theodorica; Shadiq, Raihan; Farida, Leny Silviana (Asian Journal of Health Research, 2025)
Introduction: Sexual dysfunction is a common concern among postmenopausal women. Testosterone therapy has been proposed as a treatment option, yet evidence remains inconsistent.    Material and Methods: We searched PubMed, ScienceDirect, and EBSCOhost (January 2010–December 2024). Randomized controlled trials (RCTs) assessing testosterone versus placebo or control in postmenopausal women were included. Data extraction and synthesis were performed independently by two reviewers. Risk of bias was assessed using the Cochrane RoB 2 tool. RevMan 5.4 was used for meta-analysis.    Results: Seven articles were considered relevant for assessing the effect of testosterone or androgen therapy on sexual function and desire of postmenopausal women (n = 711). The testosterone group showed significant improvement in sexual activity or desire (OD: 3.18, 95% CI: 2.53 - 3.98, p< 0.00001). This result shows that testosterone therapy has the potential to improve sexual activity and desire in postmenopausal women.    Conclusion: Testosterone therapy may improve sexual function in postmenopausal women, but heterogeneity and limited long-term safety data warrant caution. Further high-quality RCTs are needed.